Becoming a hominid: Notes on the early taxonomy of Australopithecus - Štrkalj, Goran (Anthropological Review, 2000)
The paper attempts to trace the first suggestions that the Australopithecus should be classified as a hominid. It would appear that the first classification of Australopithecus as a member of the family Hominidae is to be found in the works of the German anthropologist Paul Adloff and the American scientist Dudley J. Morton. Adloff.s and especially Morton.s views, although largely neglected at the time when they were first articulated, represent the first steps towards the modern position on the taxonomy of Australopithecus.